Delayed presentation of diaphragmatic hernia as acute intestinal obstruction due to an old penetrating trauma: a rare case report - Biswas, Prakash; Yadav, Neha; Sridhar, Rachith; Bhatia, P. K.; Patel, Binoy (International Surgery Journal, 2020)
Acquired diaphragmatic hernias (ADH) are uncommon following penetrating thoraco-abdominal injuries. This is a case report of ADH with bowel obstruction following an old penetrating abdominal trauma without any signs and symptoms of respiratory distress.